2010
DOI: 10.3844/ajabssp.2010.397.402
|View full text |Cite
|
Sign up to set email alerts
|

Fungal Culture Systems for Production of Antioxidant Phenolics Using Pecan Nut Shells as Sole Carbon Source

Abstract: Problem statement: Many agro-industrial wastes have little or none utilization, when these materials could be a very rich source of several value-added compounds, such as: the pecan nut shells, which contain Antioxidant Phenolic (AP) molecules like tannins. Approach: In this study, a bioprocess for the liberation of AP from Pecan Nut Shells (PNS) was described. A chemical characterization of raw material was evaluated to determine polyphenolic content of PNS, among other … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 20 publications
1
3
0
Order By: Relevance
“…In general, the growth profile was similar to that reported by Shin et al (2019) for A. oryzae and Aspergillus awamori ( A. awamori ) using black rice bran as substrate. Medina et al (2010) also observed similar results in their study with PWS and Aspergillus niger ( A. niger ). However, differences were observed in the amount of A. oryzae recovered from fermented PWS or PWSE at different times, representing different fungal growth rate depending on the substrate (Figure 1).…”
Section: Resultssupporting
confidence: 80%
“…In general, the growth profile was similar to that reported by Shin et al (2019) for A. oryzae and Aspergillus awamori ( A. awamori ) using black rice bran as substrate. Medina et al (2010) also observed similar results in their study with PWS and Aspergillus niger ( A. niger ). However, differences were observed in the amount of A. oryzae recovered from fermented PWS or PWSE at different times, representing different fungal growth rate depending on the substrate (Figure 1).…”
Section: Resultssupporting
confidence: 80%
“…In general, the growth profile was similar to that reported by for A. oryzae and A. awamori using black rice bran as substrate. (Medina et al, 2010) also observed similar results in their study with pecan walnut shell and Aspergillus niger. However, differences were observed in the amount of A. oryzae recovered from fermented PWS or PWSE at different times, representing different fungal growth rate depending on the substrate (Figure 1).…”
Section: Phenolic Acid Profilesupporting
confidence: 79%
“…This strain is reported as tannin-degrading (Mata-Gomez et al, 2009). In a previous study (Medina et al, 2010), using the Aspergillus strain, solid cultures were made and the fungi could proliferate on the system which was tannin-rich. In the case of the actual cultures of this study, the tannin absence, possibly affects the growth of another strains, such as Aspergillus.…”
Section: Discussionmentioning
confidence: 99%
“…Cellulolytic enzyme production has acquired great importance due mainly to the interest in exploiting lignocellulose as energy source. Pecan nut shells (Carya illinoensis) consists on the major component of the nut and also the main residue generated in the use of this alimentary product (Medina et al, 2010). The strong association between cellulose, hemicellulose and lignin limits the application of these residues on certain processes, such as biomolecules and biofuels (Faria-Martins et al, 2008, Daoud andAlam, 2010).…”
Section: Introductionmentioning
confidence: 99%